2000
DOI: 10.1590/s0004-28032000000200004
|View full text |Cite
|
Sign up to set email alerts
|

Neoplasias primárias múltiplas em pacientes com câncer colorretal

Abstract: The prevalence of multiple primary neoplasms was of 3.4%, being major in female. Uterus' cancer was the more frequent association. Radiotherapy was performed in 40% of patients. We believe that attendance of cancer patients is very important to precocious diagnosis and treatment of multiple primary neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Second pCRC affects the same site but is anatomically distinct from the initial pCRC and thus is not a metastatic or recurrent tumor from the initial pCRC [ 7 , 9 11 ]. With respect to the prognosis of patients with initial and second pCRC, Hildebrand et al [ 11 ] observed that there were no significant differences on the prognosis of 1,500 patients with or without multiple primary colorectal cancers who underwent surgery, including those with second pCRC; however, the prognostic analysis was not based on a nationwide dataset or stratified by age at diagnosis and postoperative pathological stage (pTNM stage).…”
Section: Introductionmentioning
confidence: 99%
“…Second pCRC affects the same site but is anatomically distinct from the initial pCRC and thus is not a metastatic or recurrent tumor from the initial pCRC [ 7 , 9 11 ]. With respect to the prognosis of patients with initial and second pCRC, Hildebrand et al [ 11 ] observed that there were no significant differences on the prognosis of 1,500 patients with or without multiple primary colorectal cancers who underwent surgery, including those with second pCRC; however, the prognostic analysis was not based on a nationwide dataset or stratified by age at diagnosis and postoperative pathological stage (pTNM stage).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in developed countries and certain regions of Africa, where respectively hernia and volvulus of the colon represent the second leading cause of intestinal obstruction (1,9) , we observed high proportion of cancer incidence. We think that this is due to the socio-economic context of our country, in which patients seek medical care in large emergencies of public hospitals with intra-abdominal tumors in advanced stage of evolution (3) .…”
Section: Discussionmentioning
confidence: 99%